Electrocardiogram signal classification and machine learning emerging research and opportunities - Moein, Sara, 1983- (Advances in medical technologies and clinical practice book series., 2018)
"This book develops an intelligent system to classify electrocardiogram signal classification signals for 4 common heart disorders, which are supraventricular tachycardia, bundle branch block, anterior myocardial infarction (Anterior MI), and inferior myocardial infarction (Inferior MI) as well as the normal healthy class"--Provided by publisher.